Pengaruh Motivasi dan Kepemimpinan terhadap Prestasi Kerja Guru Sekolah Menengah Atas Negeri di Kota Malang - Budiantono, Bambang - (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
The purpose of this research is: 1) To understand the effects of motivation and simultaneously or partially good leadership to Public High School teacherâs achievement in Malang City .and 2) To understand the variable which have dominant effect to Public High School teachers in Malang City. Refer to F test, the result from the count of F equal to 38,663 bigger than F table which equal to 3.186, the meaning is indepentent variable (X1 and X2) simulaneaously influential to dependent variable Y (work achievement). From the test t analysis above, the conclusion is independent variable (X1 and X2) partially, significanly influence to dependent variable Y (work achievement), thus, the first hipothetic offer which is by partially granted. There is variable which gives dominant influence, the leadership variable become dominant factor in influencing teacherâs work achievement by seeing from te biggest Â stratndardized is leadership which equal to 0,544 or 54,5% Keywords: Motivation, Leadership, and Work Achievement